Mechanics based solution for predicting deflection and ultimate load of ordinary and plated-reinforced concrete beams - El-Zeadani, Mohamed Hassan Hamad (2019)
Most design codes available today use full-interaction moment-curvature analysis to determine the deflection and moment capacity of reinforced concrete (RC) beams. This has been achieved by calibrating design equations with hundreds of lab tests to ensure their validity. While this has worked well for steel reinforced RC structures, the derived design equations cannot be used for RC structures with different types of reinforcement material. Alternatively, mechanics-based methods that take into consideration the partial- interaction behavior between the reinforcement and adjacent concrete, and also the size and shape effect of the concrete in compression can be used. The main objective of this study was to develop mechanics-based solutions for RC beams and CFRP plated RC beams to determine their deflection and ultimate load carrying capacity. The results from the mechanics-based methods were compared with the experimental results of three RC beams and three CFRP plated RC beams that were subjected to a point load at mid-span. A comparison between the analytical results and experimental results showed a good agreement between the deflection and ultimate load results for the RC beams. For instance, the difference between the theoretical and experimental ultimate loads for the RC beams considered was merely 0.92%. Good agreement was also observed in the recorded strains in the reinforcement steel at the center of the beam. However, for the CFRP plated beams, the results derived from the mechanics-based solution indicated an early yielding of the reinforcement steel which caused poor correlation of the results at higher applied loads. For example, the theoretical and experimental ultimate loads varied by about 34%. This was attributed to the fact that the strain in the CFRP plate was assumed to remain constant once the intermediate crack (IC) debonding strain was achieved; however, in reality the strain in the plate kept building up until debonding of the plate took place. A parametric study that allowed for shear stresses to develop in the plate after the IC debonding strain was achieved showed a better correlation with the experimental results at higher applied loads for the deflection and ultimate load carrying capacity (difference in ultimate load being less than 5%).